Andrzej jak Architekt. O projektach Andrzeja Tomaszewskiego - Repucho, Ewa; Krzak-Weiss, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The aim of the article is to present one of the key figures in the contemporary book market, Andrzej Tomaszewski, who is a remarkable designer, typographer, printer as well as a bibliophile, teacher and populariser of knowledge about books. Our goal in this article is to present him particularly as an outstanding book architect expertly skilled in the use of the polygraphic “trowel” who possesses and effectively uses his deep knowledge of all the nuances of designing for print. To this end, we present Tomaszewski’s selected designs, closely scrutinising them in order to highlight his versatility and the diversity of his skills.